A DRAIN‐SPACING EQUATION THAT TAKES THE HORIZONTAL FLOW IN THE UNSATURATED ZONE ABOVE THE GROUNDWATER TABLE INTO ACCOUNT1. (15th January 2014) - Yousfi, A.; Mechergui, M.; Ritzema, Henk
ABSTRACT Most drain spacing calculations do not take the horizontal flow in the unsaturated zone above the groundwater table into consideration. In this paper, a solution is presented that includes the contribution of unsaturated flow above the groundwater table. Drain spacing calculated with the newly derived equation is compared to that calculated with the Hooghoudt equation and the two‐dimensional Hydrus‐2D model. Results show that drain spacing calculated with the new equation results in a wider value. The effects are most pronounced for tiles located close to the impervious layer, particularly in coarse, sandy soils. These effects rapidly decrease if the depth of the impervious layer increases. The effect of the unsaturated zone flow contribution is limited to sandy soils, for low infiltration ratios and tiles placed on top of an impervious layer. The maximum increase in drain spacing calculated by the new formula is about 30% higher, suggesting that inclusion of the contribution of the unsaturated zone flow in the computation of drain spacing may result in greater economy in the design of subsurface drainage systems. Moreover, the new equation is more general and is applicable for tiles lying on or far from an impervious layer. Copyright © 2014 John Wiley & Sons, Ltd.